2009
DOI: 10.1111/j.1365-2966.2009.14402.x
|View full text |Cite
|
Sign up to set email alerts
|

Mock galaxy redshift catalogues from simulations: implications for Pan-STARRS1

Abstract: We describe a method for constructing mock galaxy catalogues which are well suited for use in conjunction with large photometric surveys. We use the semi‐analytic galaxy formation model of Bower et al. implemented in the Millennium N‐body simulation of the evolution of dark matter clustering in a Λ cold dark matter cosmology. We apply our method to the specific case of the surveys soon to commence with PS1, the first of four telescopes planned for the Pan‐STARRS. PS1 has five photometric bands, g, r, i, z and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…All three sets contain the nominal NIR photometry expected from Euclid but have different choices for the depth in grizy , and therefore explore the requirements for the ground‐based complement of the IR survey. Survey‐A, which we generally find to be inadequate, uses the point‐source sensitivities from Cai et al (2009). This is therefore a possibly optimistic representation of a PS‐1‐like survey.…”
Section: Generation Of the Photometric Cataloguesmentioning
confidence: 99%
“…All three sets contain the nominal NIR photometry expected from Euclid but have different choices for the depth in grizy , and therefore explore the requirements for the ground‐based complement of the IR survey. Survey‐A, which we generally find to be inadequate, uses the point‐source sensitivities from Cai et al (2009). This is therefore a possibly optimistic representation of a PS‐1‐like survey.…”
Section: Generation Of the Photometric Cataloguesmentioning
confidence: 99%
“…Hence separating galaxies into redshift bins strongly improves the constraining power of cosmic shear on cosmological model parameters (Hu 1999). Extensive studies have been reported in the literature that look for optimal configurations of redshift binning and requirements for future ambitious surveys, covering several thousand square degrees, (Amara & Réfrégier 2007;Banerji et al 2008;Cai et al 2009;Sun et al 2009;Bernstein & Huterer 2010;Abdalla et al 2008;Bellagamba et al 2012;Bordoloi et al 2010Bordoloi et al , 2012Sheldon et al 2012;Cunha et al 2014). In addition to gains in statistical precision, separating galaxies into tomographic bins can also mitigate astrophysical systematics.…”
Section: Introductionmentioning
confidence: 99%
“…[40] and [32], respectively, while we denote Pan-STARRS as a wide shallow galaxy survey [44]. TABLE II.…”
Section: B Resultsmentioning
confidence: 99%